(untitled) (International Journal of Engineering Management Science, 2018)
The durability of concrete structures plays a significant role in modern construction, especially in aggressive environments. This work discus ses the impact of nano-silica (NS) and rice husk ash (RHA) substitution as a partial cement replacement in concrete in order to improve the durability of concrete. This paper discusses the supplementary cementitious materials (SCMs) together with their synergy concerning mechanical properties, sulfate resistance, chloride ion penetration, water absorption, and carbonation depth. Experimental studies were conducted based on the ASTM standards for consistency and reliability. Incorporation of NS and RHA improves the pozzolanic reaction, resulting in a finer microstructure and reduced permeability, thus improving the durability of concrete. Significant improvements in the strength and durability characteristics have been seen compared with the conventional concrete. This work sheds light on sustainable construction by utilizing industrial by-products and helps in the reduction of cement consumption, hence, lowering environmental impacts. The result reveals that the durability of NS and RHA could enhance concrete service life for the structure.